Physical Resistance Analysis Of Football Players In Ssb Abhiseva U-16 Limun Cage Bengkulu City - Anggi Oxiander; Mesterjon Mesterjon; Mariska Febrianti (Perkumpulan Dosen Muda Bengkulu, 2021)
This research is a quantitative descriptive research. The method used is the method of analysis. The subjects of this study were 24 SSB Abhiseva U-16 players in Bengkulu City. The instrument used was the Bleep Test. The analysis technique used is to pour the frequency into the form of a bar chart. The results of this study indicate that the level of endurance of SSB Abhiseva Kandang Limun players in Bengkulu City is very low considering the highest frequency with very low category with 18 people or 75%. Analysis of the Physical Endurance of football players at SSB Abhiseva Kandang Limun in Bengkulu City which is categorized as very good 0 people or 0%, either 0 people or 0%, moderate 0 people or 0%, less 6 people or 25%, less 18 people or 75 %.